The major future economic challenges: What are the lessons to be learned and possible solutions for Indonesia? - Cut Muftia Keumala; Neni Triana (Sekolah Tinggi Ilmu Administrasi Nasional, 2022)
This review study aims to understand the current phenomena and major future global economic challenges and their impact on Indonesia. We also propose a solution to the issue. This conceptual article aims to explain and clarify complex ideas and provide insights into a phenomenon's underlying structure or nature. This study recommends Indonesia should consider several suggestions to prepare for global economic challenges. The government may focus on infrastructure. Infrastructure improvements will boost Indonesia's economy, create jobs, and attract investment. Strong infrastructure improves goods and people movement, transaction costs, and economic efficiency. Infrastructure spending increases competitiveness, job creation, and private investment. Indonesia can become more competitive by eliminating bureaucracy and corruption, improving investment conditions, and encouraging innovation. Competitive economies make better, cheaper, and more efficient products. This can boost investment, jobs, and living standards. Furthermore, exports open new markets, boost demand for manufactured goods, and generate foreign currency. Developing Indonesia's human capital is also crucial. Besides, gender equality requires removing workplace barriers for women. This boosts the labor force and economic growth. Human capital development boosts long-term economic growth and competitiveness. Government should address income inequality. Progressive taxation, social safety nets, and job creation reduce income disparity and increase consumer spending.